Analisis Strategi Power Play Permainan Futsal Tim Halus FC pada Liga Futsal Profesional Indonesia Tahun 2023/2024 Pekan 1-8 - Fuadien, Hakim Aziz Nur; Anam, Khoiril (MAN Insan Cendekia Jambi, 2024)
The aim of this research is to determine the percentage of success in using the power play strategy and determine the factors that cause power play to fail for the Halus FC team in the 2023/2024 Indonesian Professional Futsal League weeks 1-8. The method used in this research is a ex post facto method on the YouTube channel to analyze the percentage of success in using the power play strategy and find out the factors that caused the power play strategy to fail for the Halus FC team in the Indonesian Professional Futsal League 2023/2024 weeks 1-8. Based on the research results, it can be concluded that from 105 trials of the power play strategy, the percentage of success was 6.7% or 7 successful trials. The dominant factor that caused the strategy to fail was 34 shooting blocks, followed by 29 inaccurate shooting, 26 inaccurate passing, 5 out of control, and 4 off the dribble attempts. The average remaining duration of the FC soft team when using the power play strategy occurred in the last 05.33 minutes remaining. And the average use of the power play strategy is 16 seconds.